Pengaruh Laju Pertumbuhan, Kontribusi dan Potensi Pajak Bumi Dan Bangunan Terhadap Penerimaan Pajak Dalam Negeri Tahun 2020 – 2022 - Ferinda Yuni Yanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Land and Building Tax is a type of tax that applies in Indonesia. As a type of direct tax, Land and Building Tax has an important role in domestic tax revenue. This study aims to determine the effect of the growth rate, contribution and potential of Land and Building Tax on Domestic Tax Revenue. By using purposive sampling as a method for determining the sample and statistical testing in the form of descriptive analysis, classic assumption test and partial t test as a reference for testing the hypothesis, the results obtained are that the results of the t-test variable growth rate of Land and Building Tax is 1.127 with a significance level of 0.263. Significance value 0.263 > 0.05. Based on the test results, it can be stated that the variable growth rate of Land and Building Tax has no effect on the variable Domestic Tax Revenue. The results of the t-test variable contribution of Land and Building Tax is 11.572 with a significance level of 0.000. Significance value 0.000 <0.005. Based on this test, it can be stated that the Land and Building Tax Contribution variable has a positive and significant influence on Domestic Tax Revenue. The result of the t-test for the variable potential for Land and Building Tax is 2.242 with a significance level of 0.027. Significance value 0.027 > 0.05. Based on the test results, it can be stated that the potential variable of Land and Building Tax has no positive and insignificant influence on Domestic Tax Revenue.